Overeducation and Overskilling: Second generation Australians - Messinis, G (My University, 2008)
This study utilises HILDA data to evaluate the performance of second generation Australians in full-time employment over the period 2001-2005. Attention is paid to the effects and key drivers of overeducation and overskilling. Quantile regression is employed to account for non-random sample selection. The evidence provides several new insights: (a) Greek-Australians are overeducated; (b) Asian languages and Chinese or Vietnamese ancestry associate with a wage premium; (c) the returns to tertiary education, overeducation and overskilling very with ability; (d) parental occupational status is a key determinant of overeducation; and (e) lack of employer provision for new skills and personality traits are important drivers of overskilling.
Centre for Stategic Economic Studies Working Paper
Keywords: Employment; Culture -- Culturally and Linguistically Diverse; Culture; Labour market; Employment; Culture; Culturally and Linguistically Diverse; Employment and unemployment